Hawkinsinuria With Direct Hyperbilirubinemia in Egyptian-Lebanese Boy - El Khatib, Hassan; Asaad, Bilal; Zaylaa, Aisha; Awad, Farah; Sbeity, Mariam; Mneimneh, Sirin; Haber, Georges; Naja, Zeina; Rajab, Mariam (Frontiers in Pediatrics, 2019)
Tyrosinemia type III is the rarest type of tyrosinemia, because of a mutation in 4-OH-phenylpyruvate dioxygenase (HPD). This causes two different types of diseases with different mode of inheritance: tyrosinemia type III and hawkinsinuria. Hawkinsinuria is an autosomal dominant disease, which present with failure to thrive and metabolic acidosis; however, the liver is not affected. Urinary excretion of hawkinsin, a sulfur amino acid, throughout life and symptoms improve during the first year of life. P.A33T heterozygous mutation was reported by Tomoeda et al. that causes hawkinsinuria. This case will report the first case of an Egyptian-Lebanese male that developed direct hyperbilirubinemia and was found to have tyrosinemia type 3 due to elevated tyrosine level in blood and tyrosine derivatives in urine, but genetic testing revealed P.A33T heterozygous mutation, a case of hawkinsinuria.